Aplikasi Model Loyalitas Berbasis Relationship Quality Dalam Pengelolaan Dunia Pendidikan Tinggi: Sebuah Pandangan Komprehensif dan Tantangan Bagi Peneliti - Licen Indahwati Darsono (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2010)
As a result of tight competition in the higher education sector, loyalty creation become important issues. However, empirical studies of this issue are still lacking. Yet, many empirical investigation of loyalty and relationship quality only use single perspective. Comprehensive perspective on internal-external customer, loyalty-disloyalty are used for proposing relationship-based loyalty model. Further, several higher education management pattern in Indonesia are discussed and reviewed. Theoretical contribution of this articles lies on spiral effect of loyalty/disloyalty-performance relationship, expanding arena of Ioyalty studies on higher education sector. Practical contribution of this articles lies on practical guide for managing loyalty in higher education. Several challenges for future research are also discussed and reviewed.